Estimation of Surface Runoff In Northeastern Missan Governorate by Using (Nrcs-Cn) Technique And Gis - Atiaa, Alaa M.; Aljabbari, Mukdad H.; M.Al-Shamma’a, Ayser (Sulaimani Journal for Pure and Applied Sciences, 2014)
In this study, an attempted was made to estimate average of annual total surface runoff in the northeastern Missan Governorate, south of Iraq by using Natural Resources Conservation Services Curve Number (NRCS – CN) empirical technique in GIS platform. Thematic layers of soil hydrological groups and LULC were created using ArcGIS 9.3 software. Intersection of these two thematic layers generated a map with new polygons representing the merged hydrological soil group and LULC. The appropriated CN values adapted from different sources and technical release of United State of Department of Agriculture (USDA) were assigned manually for each new merged polygon. The curve numbers for different antecedent moisture content (AMC) were calculated as 38, 59, 77 for dry, normal, and wet soil conditions. The associated maximum potential retention for each AMC were calculated as 75,87, 176.51, and 414.42 for dry, normal, and wet soil moisture conditions. Application of the method showed that the average annual runoff depth is 0.36 mm. This figure was multiplied by the area of the study area (1856) km2 to get the total average of runoff volume 7424000m3 which represents 0.0003 from the total annual average of rainfall. The applied method is robust and easy to implement and could be used to roughly estimate the surface runoff with minimal data.
Keywords: Surface runoff; NRCSCN technique; GIS; Missan Governorate; Iraq